DNA Barcoding Coupled with High Resolution Melting Analysis Enables Rapid and Accurate Distinction of Aspergillus species. (3rd December 2016) - Fidler, Gabor; Kocsube, Sandor; Leiter, Eva; Biro, Sandor; Paholcsek, Melinda
Abstract: We describe a high-resolution melting (HRM) analysis method that is rapid, reproducible, and able to identify reference strains and further 40 clinical isolates of Aspergillus fumigatus (14), A. lentulus (3), A. terreus (7), A. flavus (8), A. niger (2), A. welwitschiae (4), and A. tubingensis (2). Asp1 and Asp2 primer sets were designed to amplify partial sequences of the Aspergillus benA (beta-tubulin) genes in a closed-, single-tube system. Human placenta DNA, further Aspergillus (3), Candida (9), Fusarium (6), and Scedosporium (2) nucleic acids from type strains and clinical isolates were also included in this study to evaluate cross reactivity with other relevant pathogens causing invasive fungal infections. The barcoding capacity of this method proved to be 100% providing distinctive binomial scores; 14, 34, 36, 35, 25, 15, 26 when tested among species, while the within-species distinction capacity of the assay proved to be 0% based on the aligned thermodynamic profiles of the Asp1, Asp2 melting clusters allowing accurate species delimitation of all tested clinical isolates. The identification limit of this HRM assay was also estimated on Aspergillus reference gDNA panels where it proved to be 10–10 2 genomic equivalents (GE) except the A. fumigatus panel where it was 10 3 only. Furthermore, misidentification was not detected with human genomic DNA or with Candida, Fusarium, and Scedosporium strains. Our DNA barcoding assay introduced here provides results within a few hours, and it may possess further diagnostic utility when analyzing standard cultures supporting adequate therapeutic decisions.